Forecasting the number of births in Poland using leading indicators - Krupowicz, Joanna (Prognozowanie liczby urodzeń w Polsce z wykorzystaniem zmiennych wyprzedzających, 2011)
The concepts of leading and lagging indicators are of great use in studies of cyclical fluctuations in economic phenomena. The article discusses the possible application of the concepts in analysing and forecasting the birth process in Poland. The article was designed to use leading indicators for projecting the number of births in Poland. For the reference variable (the number of births), leading indicators were sought in the set of potential demographic variables. The set comprised variables describing the structural factors responsible for the birth process. A synthetic leading indicator was constructed and then the projected numbers of births in Poland for 2006-2015 were computed. Subsequently, the projections for the years 2006-2009 were verified in terms of quality.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 196, s. 124-136
Keywords: wahania cykliczne; prognozowanie; prognozowanie demograficzne; cyclical fluctuations; forecasting; demographic forecasting